2007
DOI: 10.4049/jimmunol.178.10.6316
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the IgD Binding Site of Encapsulated Haemophilus influenzae Serotype b

Abstract: Encapsulated Haemophilus influenzae is a causative agent of invasive disease, such as meningitis and septicemia. Several interactions exist between H. influenzae and the human host. H. influenzae has been reported to bind IgD in a nonimmune manner, but the responsible protein has not yet been identified. To define the binding site on IgD for H. influenzae, full-length IgD and four chimeric IgDs with interspersed IgG sequences and Ag specificity for dansyl chloride were expressed in stably transfected Chinese h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In fact, nonimmune binding of Igs by gram-positive bacteria is relatively common but rare among gram-negative bacteria (51,75). Interestingly, H. influenzae also displays a strong affinity for soluble human IgD (125), although the protein involved in IgD binding has as yet been identified only in M. catarrhalis. MID is also a B-lymphocyte mitogenic stimulant that initiates Ig production (49), and a comparison of MIDs of five strains revealed that the overall sequence identity ranged between 65.3% and 85.0%, with some regions showing an identity up to 97% (98).…”
Section: Adhesion and Major Ompsmentioning
confidence: 99%
“…In fact, nonimmune binding of Igs by gram-positive bacteria is relatively common but rare among gram-negative bacteria (51,75). Interestingly, H. influenzae also displays a strong affinity for soluble human IgD (125), although the protein involved in IgD binding has as yet been identified only in M. catarrhalis. MID is also a B-lymphocyte mitogenic stimulant that initiates Ig production (49), and a comparison of MIDs of five strains revealed that the overall sequence identity ranged between 65.3% and 85.0%, with some regions showing an identity up to 97% (98).…”
Section: Adhesion and Major Ompsmentioning
confidence: 99%
“…However, the bacteria can also be invasive in tonsillar tissue. By binding to surface IgD at the CH1 region, it is postulated to function as a superantigen . In vitro experiments have shown that H. influenzae , and also OMV‐mediated sIgD cross‐linking, result in strong proliferation of IgD+ lymphocytes, secretion of poly‐reactive IgM and IgD, production of IL6, and sensitization to BAFF .…”
Section: Discussionmentioning
confidence: 99%
“…Hypothetically, the nonimmuneactivated B cells that change from IgD ϩ /IgM ϩ to IgD -/IgM ϩ Representative results from one out of four donors are shown, and corresponding geometric mean fluorescence, SD, and P values are presented in Table 3. will later be negatively selected during affinity maturation. B cells that keep the IgD receptor will be favored in the process, and this could explain the high number of IgD ϩ plasma cells in the nasopharynx and in the middle ear cavity, areas that are frequently colonized by two pathogens (M. catarrhalis and H. influenzae) capable of binding IgD [14,[42][43][44].…”
Section: Discussionmentioning
confidence: 99%